PEMBELAJARAN BAHASA INDONESIA TINGKAT DASAR DENGAN PERMAINAN CATURJANTRA - Eunice W. Setyaningtyas (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
This qualitative research discussed some literatures and gives suggestions of teaching ideas and methods for language learning using games in the classroom. Withliterature study methods, it could be deeper understood that language learning needscommunicative and cooperativeapproach, without leaving a challenging and funatmosphere and better if the learrning is adjusted according to students characteristics.One of the ways is through the use of ‘Catur Jantra’ game with these steps: 1)stimulation, 2) exploration, 3) structure learning, 4) ‘Catur Jantra’, 5) evaluation andreflection. This game is still open for modification appropriate to learning topics and students’ need as one of the ways to apply the differentiation strategy in the class. Thisidea brought some theoretical and practical implications for effective learning. It issuggested teachers apply this game method to facilitate the students, for native speakerslearners as well as to foreign/ second language learners, in attempts of their fluency inIndonesian language learning. Keywords: Indonesian language learning, Catur Jantra game, communicative, active learning.